Magnetizing Creative Talent: The Influences of Creative Ecology on Spatial Behavior of Creative Class in Charoen Krung District - Janjamlah, Tipsuda; Kaewlai, Peeradorn (Journal of Architectural/Planning Research and Studies (JARS), 2020)
The objective of this research is to find the components of the spatial behavior and the creative ecology in Charoen Krung district, and develop the relationship model between the two variables. The research methods used are both qualitative and quantitative techniques to analyze both the exploratory and second-order confirmatory factor analysis of 450 creative people data collected, and develop the relationship between variables by analyzing the Structural Equation Model. The results of the research showed that the spatial behavior of creative people can be divided into 2 characteristics which are (1) the habitual usage, and (2) the purposive usage. The creative ecology is divided into 2 types which are (1) the area that directly connects work and creative business activities (connectors), and (2) the areas that encourage creative activities (enablers). The study of the influence of the creative ecology that effect creative people’s behavior found that all spatial behaviors are significantly influenced from the connector group, and did not found a significant influence on the enablers group. Those involved in the development of the creative district can apply these findings to prioritize development that is consistent with the demand of creative users who are key users.